DIVERSITATSSENSIBLE PADAGOGINNENBILDUNG IN FORSCHUNG UND PRAXIS;UTOPIEN, ANSPRUCHE UND HERAUSFORDERUNGEN - ROBERT SCHNEIDER-REISINGER;MANFRED OBERLECHNER (Verlag BARBARA BUDRICH, 2020)
The volume presents experiences from and reflections on inclusive universities in contributions from various scientific fields and methodological traditions. The book is a "landmark" of a corresponding reform/transformation process with a focus on research, teaching and university practice in the face of the tension between person and institution. The aspect "performance and diversity or plurality" is explicitly addressed, and in connection with structural and resource questions the utopian content is constructively confronted with the practice-relevant challenges of pedagogical education.